A randomized pilot study with daily walking during adjuvant chemotherapy for patients with breast and colorectal cancer. (April 2014) - Backman, Malin; Wengström, Yvonne; Johansson, Birgitta; Sköldengen, Ida; Börjesson, Susanne; Tärnbro, Sara; Berglund, Åke
Abstract Background. Physical activity during chemotherapy has been shown in several studies to reduce fatigue, improve symptoms and impact positively on health-related quality of life (HRQoL). Challenges associated with intervention studies on physical activity during cancer treatment relate to consistent adherence. The primary objective was to study feasibility and adherence of physical activity intervention among patients with cancer during adjuvant chemotherapy treatment. The secondary objective was to investigate the effects of physical activity on health aspects, including HRQoL, symptoms and surrogate markers for cardiovascular disease. Material and methods. This randomized controlled trial included patients with breast cancer (BRCA) and colorectal cancer (CRC) during adjuvant chemotherapy. The intervention continued for 10 weeks and included daily walks of 10 000 steps and a weekly supervised group walk. Adherence was assessed by a pedometer and the number of participants who reported step counts every week and percentage of participants who achieved the target steps every week. Results. Adherence average reached 91% during the intervention period; in total 74% completed the exercise intervention. The majority of the participants achieved an average of 83% of the target of 10 000 steps per day for 10 weeks. There was a significant increase in daily physical activity (p = 0.016) in the intervention group. Significant differences were also found for some breast cancer-specific symptoms [swelling, mobility and pain (p = 0.045)]. The study showed a relatively small weight gain an average of 0.9 kg in the intervention group and 1.3 kg in the control group. Conclusion. Physical activity in the form of walking is feasible during adjuvant chemotherapy treatment despite increasing symptoms. The physical activity increased in the intervention group during the study time and had a positive impact on breast symptoms and the weight gain was lower in comparison to previous studies.